Co-circulation of both low and highly pathogenic avian influenza H5 viruses in current poultry epidemics in Taiwan. Issue 1 (30th June 2020) - Li, Yao-Tsun; Chen, Chen-Chih; Chang, Ai-Mei; Chao, Day-Yu; Smith, Gavin J D
Abstract: Highly pathogenic avian influenza (HPAI) A(H5) viruses belonging to clade 2.3.4.4c of the A/goose/Guangdong/1/96-like (Gs/GD) lineage caused severe global outbreaks in domestic birds from 2014 to 2015, that also represented the first incursions of Gs/GD viruses into Taiwan and the USA. However, few studies have investigated the circulation of clade 2.3.4.4c viruses after 2015. Here, we describe Gs/GD clade 2.3.4.4c and Mexican-like H5N2 viruses that were isolated in Taiwan during active surveillance conducted in chicken farms from February to March 2019. Phylogenetic analysis demonstrated two distinct genome constellations of the clade 2.3.4.4c H5 viruses, with the internal genes of one of the new genotypes closely related to a virus isolated from a pintail ( Anas acuta ) in Taiwan, providing the first direct evidence that migratory birds play a role in importing viruses into Taiwan. Our study also confirmed the co-circulation of Gs/GD clade 2.3.4.4c and Mexican-like H5 lineage viruses in Taiwan, presenting a rare case where Gs/GD viruses developed sustained transmission alongside another enzootic H5 lineage, raising the possibility that homosubtypic immunity may mask virus transmission, potentially frustrating detection, and the implementation of appropriate control measures. To eradicate H5 viruses from poultry in Taiwan, further studies on the effect of co-circulation in poultry of low pathogenic avian influenza and HPAI viruses are needed. Furthermore, only with continued surveillance efforts globally can we fully discern dispersal patterns and risk factors of virus transmission both to and within Taiwan.